The Going Concern Paradigm in Bankruptcy Process Reviewed from Regulations in Indonesia - Bernard Nainggolan; Kostruba Anatoliy (Jurnal Hukum, 2024)
Companies often seek alternative debt resolution methods in bankruptcy to avoid liquidation or operational shutdown. One such alternative is through a settlement, where the debtor offers partial payment of the debt to creditors with the condition of being released from the remaining debt. Additionally, the suspension of debt obligations allows companies to develop a financial restructuring plan that can ensure long-term operational sustainability. Thus, the purpose of this study is important to understand how bankruptcy decisions, and debt settlement alternatives for business actors and stakeholders. This research uses a descriptive approach by analyzing relevant legislation, legal literature, and case studies to understand the mechanisms and legal implications of the bankruptcy process. The secondary data used comes from sources such as laws, court rulings, and relevant legal literature. The primary focus of this research is to analyze Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The study results indicate that the bankruptcy process in Indonesia relies on mechanisms such as debt payment suspension, settlement, and judicial review to resolve debts and ensure business continuity. The going concern paradigm is integrated into these processes, although in a different context from the principle in civil law.